2002
DOI: 10.1042/bj3640121
|View full text |Cite
|
Sign up to set email alerts
|

Plant-derived phenolic compounds prevent the DNA single-strand breakage and cytotoxicity induced by tert-butylhydroperoxide via an iron-chelating mechanism

Abstract: The protective effects of selected members from a series of caffeic acid esters and flavonoids were tested in various toxicity paradigms using U937 cells, previously shown to be sensitive to either iron chelators or bona fide radical scavengers or to both classes of compounds. It was found that all the protective polyphenols were active at very low concentrations and that their effects were observed only under those conditions in which iron chelators also afforded protection. Consistently, active polyphenolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
82
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(91 citation statements)
references
References 29 publications
7
82
0
2
Order By: Relevance
“…It was reported that phenolics' metal chelating power is determined by their chemical structures and the availability of properly oriented functional groups, with six-membered ring complexes exhibited stronger chelating potential than five-membered ring structures [19]. Additionally, the study showed the significant contribution from catechol moiety toward metal-chelating activity [20]. Proteins and polysaccharides had also been implicated in metal-chelating activities [18].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that phenolics' metal chelating power is determined by their chemical structures and the availability of properly oriented functional groups, with six-membered ring complexes exhibited stronger chelating potential than five-membered ring structures [19]. Additionally, the study showed the significant contribution from catechol moiety toward metal-chelating activity [20]. Proteins and polysaccharides had also been implicated in metal-chelating activities [18].…”
Section: Discussionmentioning
confidence: 99%
“…Many phenol substances of plant origin or synthetic products and some salicylic acid derivatives as aspirin exhibit certain antioxidant and antiproliferative activities. [3][4][5][6][7][8][9][10][11][12][13][14] Bearing the above in mind, one part of the present research was directed to the microwaveinduced synthesis of some new derivatives of salicylic acid, starting from different amino alcohols, diamines and diols, as well as to the determination of their antioxidant and antiproliferative activities. Microvawe irradiation is an alternative to conventional heating for introducing energy into reactions.…”
Section: Introductionmentioning
confidence: 99%
“…This plant had several poly-phenolic compounds which possess this anti-oxidant activity because; flavonoids of Achillea spp. have one catechol in one of aromatic rings and two hydroxyl groups which are necessary in such activity (Sestili et al, 2002).…”
Section: Discussionmentioning
confidence: 99%